HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN INTENSI WANITA USIA 9-26 TAHUN DALAM MELAKUKAN VAKSINASI HPV DI WILAYAH KERJA PUSKESMAS KEBAGUSAN - Fauziah Mawaddah (2023)
One of the main preventions in preventing cervical cancer is to vaccinate against HPV. WHO recommends HPV vaccination for women aged 9-26 years. However, the number of HPV vaccinations in Indonesia is still low. Several factors are believed to influence the intention to vaccinate such as knowledge and attitude. This study aims to determine the relationship between knowledge and attitudes with the intention to vaccinate against HPV in the working area of the Kebagusan Health Center. This research is a quantitative study with a cross sectional approach. The number of samples in this study were 326 respondents aged 9-26 years who had never received the HPV vaccination before. Sampling was carried out by consecutive sampling at Kebagusan. Data were analyzed using univariate, bivariate and multivariate analysis. The results of the chi square test show that the two independent variables have a relationship with the dependent variable. The knowledge variable and attitude variable is related to intention (p value = 0,013 ; 0,000 < 0,05). The dominant factor related to the intention of women aged 9-26 years to vaccinate against the HPV in the working area of the Kebagusan Health Center is the attitude variable. There is a relationship between knowledge and attitudes with the intention of women aged 9-26 years in carrying out the HPV vaccination in the working area of the Kebagusan Health Center. It is hoped that health workers will be able to provide proper education about HPV vaccination so that people do not have to worry about the side effects of vaccination.